Glycolysis Role During Cold Adaptation in Ð¡arassius auratus gibelio - Relina, L. I.; Zhegunova, Ye. G.; Grischenkova, Ye. A. (Problems of Cryobiology and Cryomedicine, 2007)
The data characterizing the level of anaerobic energetic metabolism in the wild type of goldfish Carassius auratus gibelio during winter period are shown. It was determined that during winter LDH activity changed, lactate content as well as the lactate/pyruvate ratio increased for all fish tissues. Changes in LDH activity and metabolite content during temperature decrease indicate a switch of fish organism to predominantly anaerobic type if energetic metabolism under these conditions.